Gene polymorphism of Apo B (VNTR) in Egyptians with coronary artery disease - Elmougy, Rehab (Journal of Medical Biochemistry, 2021)
Abstract. Introduction. Coronary artery diseases (CAD) are a big health problem in both developed and developing countries. It is considered one of the main causes of death in the world. Accumulation of fat molecules in the blood increases the risk of CAD incidences. It is aimed here to study the impact of Apo B (VNTR) gene on CAD incidences. Subjects and Methods. Eighty CAD patients and 93 healthy volunteers are enrolled in this study. Lipid parameters were estimated in both groups and PCR technique has been performed to analyze Apo B (VNTR) gene polymorphism. Results. The genotypes 31/31, 31/37, 37/37 and 31/44 are more predominant in both groups. The frequency of 24/31 in CAD patients is (0.137) while it is completely absent in the control group. Our results show that there is an increase in the frequency of various genotypes (e.g., 17/31 and 21/34 genotypes) in the control group compared to the CAD patients group. Conclusion. 3’APOB-VNTR gene could probably be considered a risk factor in the incidences of CAD and may help to early diagnose it.